Answer:
The type of transformation is the reflection across the x-axis.
Explanation:
We are given a parent function f(x) by:
![f(x)=(2x-3)^3](https://img.qammunity.org/2019/formulas/mathematics/high-school/nx1e843kcqs9dca9h5tcgwtp1kouldhrwg.png)
and the transformed function g(x) is given by:
![g(x)=(-2x+3)^3](https://img.qammunity.org/2019/formulas/mathematics/high-school/4kndhjlllxfgujjcsu8x0s77lnjs597yd7.png)
which could also be written as:
![g(x)=(-(2x-3))^3\\\\i.e.\\\\g(x)=(-1)^3\cdot (2x-3)^3\\\\i.e.\\\\g(x)=-(2x-3)^3\\\\i.e.\\\\g(x)=-f(x)](https://img.qammunity.org/2019/formulas/mathematics/high-school/gozwxlitw27dgj9ney55mi1rdp05i2rfam.png)
i.e. the transformation g(x) is obtained by reflecting the parent function f(x) across the x-axis.
( Since, when the reflection of a function is done across the x-axis then the x-coordinate of the point of the function remains the same and the y-coordinate of the point takes the negative sign.
i.e. f(x) → -f(x)
i.e.
(x,y) → (x,-y) )